Simultaneoous Estimation of Piperne and 6-Gingerol in an Ayurvedic Formulation by HPLC - S. Kulkarni, Vishakha; J. Surana, Sanjay (Asian Journal of Chemistry, 2012)
Trikatu churna is an ayurvedic formulation used extensively by ayurvedic practitioners and contains equal amount of fine powders of rhizomes of Zingiber officinale (Zingiberaceae), fruits of Piper longum and Piper nigrum (Piperaceae). In general 6-gingerol from Z. officinale and piperine from P. longum and P. nigrum were analyzed by HPLC or by HPTLC. No analytical method is reported for the estimation of both the markers simultaneously. Trikatu churna needs simultaneous estimation of piperine and 6-gingerol. Attempt has been made to develop simple, precise, rapid and reproducible method for simultaneous estimation of piperine and 6-gingerol as a routine quality control tool of Trikatu churna. The analysis was carried out using toluene:ethyl acetate:formic acid (8:2:1, v/v/v) at room temperature. The Rf value of piperine and 6-gingerol were found to be 0.53 ± 0.04 and 0.67 ± 0.02 respectively. The method was validated by specificity, precision, recovery and robustness. Trikatu churna contains 4.38 % and 0.78 % of piperine and 6-gingerol, which were further compared with HPLC analysis.